Manual de funciones para mejorar el desempeño organizacional de la empresa Ecoquimik, matriz Machala, año 2012 - Salazar Quiroz, Vanessa Lissette (2013)
The present investigation on the elaboration of the Manual of Functions for the Company Ecoquimik, matríz Machala, has as objective to provide a document that describes and include the activities that should complete each one of the employees based on the assigned functions, and it is interesting to outline a model of organizational structure to be able to compete with the other companies, this way being able to have a competitive advantage. The summary of the information was carried out by means of the application of the investigation techniques, like they are: the survey that was applied the workers and employees of the company, with end of knowing the activities that each employee carries out; while the interview was applied the Manager Proprietor of the same one. The analysis of the results allowed knowing the grade of the workers' execution and employees to the assigned functions. It also consented to determine if the assignment of the functions has been based on the academic preparation and the professional profile that each employee possesses. As it is evident as the company has grown, the labor responsibilities are bigger, the organizational structure, is very necessary to define the positions of the company. The propuest of the present Ecoquimik, matriz Machala constitutes the design of the organizational structure, manual of functions, serving as guide toward its employees, so that they know the correct operation from the company to which belong, fomenting the responsibility and quality of its work, achieving the growth of-the-objectives-propuest.